Healthy behaviors awareness and the knowledge-practice gap among pregnant university students: an explanatory sequential study on quality of life and support services - Amnah A. Aldohan; Ahmed G. Ismail; Hany M. Hagar; Hanan M. Diab; Usama M. Ibrahem (Frontiers in Public Health, 2026)
Background Pregnant female university students face overlapping health, academic, and psychosocial demands, which can impact their quality of life and their ability to apply health knowledge in their daily lives. This study aimed to examine awareness of health behaviors, the gap between knowledge and practice, perceived quality of life, and institutional support needs among pregnant female university students. Methodology A sequential interpretive research design with mixed methodologies was employed. Quantitative data were collected from 500 pregnant female students across nine Saudi universities using validated health behavior and quality of life measures. Qualitative interviews were conducted after the quantitative data collection to interpret patterns emerging from the statistical results. Results The students reported a very high level of awareness of health behaviors during pregnancy. However, this awareness was not consistently reflected in practice. Quality of life varied, with general health and time management receiving more positive ratings than emotional and family-related areas. Qualitative findings indicated that academic pressure, limited dedicated support, social expectations, and inconsistent access to pregnancy-related services all contributed to the gap between knowledge and practice. Conclusion Awareness alone is insufficient to ensure healthy practices among pregnant university students. Universities should develop integrated support models that combine health education, flexible academic policies, counseling, and referral mechanisms to maternal health services.